The Choir Instruction for Elderly Well-Being in Case Study of The Jiazhou Choir in Leshan City, Sichuan Province, China - Mo, Chen; Klaywong, Sinam (International Journal of Multidisciplinary in Management and Tourism, 2025)
This article aims to A Study on the Training Activities for the Elderly: A Case Study of Jiazhou Choir, Leshan City, Sichuan Province, China. The research sample consisted of one choir instructor and twelve choir members from the Jiazhou Choir. Research tools included semi-structured academic interviews, along with observational analysis of rehearsal. The study employed qualitative methods, with data collection focused on both interview and observations of rehearsals. The choir has maintained its rehearsal schedule for over ten years, with the current membership totaling ninety participants, including soprano, mezzo-soprano, tenor, and baritone vocalists. Researcher identified 7 songs: 1. Jinse, 2. An Unforgettable Song, 3. Flowers and Youth, 4. Bamboo Flourishes, 5. I Heard You, 6. Camellia Flowers Bloom, 7. What is the Meaning of the Word. Rehearsals are conducted for two hours per week, with monthly practice sessions structured systematically. Training activities begin with basic vocal exercises, and continued into the song. Teaching Methods applied in 1. Lecture-Based Teaching, 2. Demonstrative Teaching 3. Interactive Teaching. Teaching Process is divided into four stages: 1. Literature Review, 2. Instructional Design, 3. Rehearsal and Performance. The Evaluation was centered on three stage: 1. Health Benefits, 2. Social Well-being, and 3. Cultural Impact. The study found that the instructional process for the Jiazhou Choir is structured, with clear procedures, systematic evaluation mechanisms, and great impact of efficiency. Structured teaching combined with consistent practice supports vocal development, longevity, and community building through music.